Embracing Diversity, Strengthening Citizen Commitment: Intercultural Dialogue and Civic Culture in The Archipelago in the Digital Era - Praja, Wina Nurhayati; Arlianty, Lia Shafira; Mahbob, Maizatul Haizan (Jurnal Kewarganegaraan, 2026)
The Indonesian archipelago confronts unprecedented challenges as digitalization reconfigures civic culture. This Systematic Literature Review investigates whether conventional intercultural dialogue strengthens civic culture or merely reproduces structural inequalities under the guise of diversity. Synthesizing 42 peer-reviewed articles from reputable databases published between 2015 and 2025, the findings reveal that everyday communication practices often marginalize minority languages. Furthermore, digital identity negotiation is algorithmically polarized rather than democratically deliberative, and local value revitalization frequently serves elite interests. The discussion highlights that these empirical findings challenge traditional pluralist models, aligning instead with the applied theory of critical multiculturalism to expose systemic power imbalances. The primary novelty of this study lies in its structural critique, arguing that intercultural dialogue without systemic transformation merely disguises inequality. In conclusion, authentic civic culture requires dismantling structural inequalities across educational systems and digital platforms, transforming diversity from a rhetorical slogan into substantive justice. This study contributes to citizenship policy by providing a transformative framework for inclusive curriculum design. Future research should empirically test these structural interventions across diverse demographics to strengthen democratic resilience.